Design of ideal vibrational signals for stinkbug male attraction through vibrotaxis experiments. Issue 12 (22nd September 2021) - Caorsi, Valentina; Cornara, Daniele; Wells, Karen E; Moser, Damiano; Berardo, Alice; Miselli, Roberto; Torriani, Michele; Pugno, Nicola M; Tasin, Marco; Maistrello, Lara; Mazzoni, Valerio
Abstract: BACKGROUND: Many groups of insects utilize substrate‐borne vibrations for intraspecific communication. This characteristic makes them a suitable model for exploring the use of vibrations as a tool for pest control as an alternative to the use of chemicals. Detailed knowledge of species communication is a prerequisite to select the best signals to use. This study explored the use of substrate‐borne vibrations for pest control of the brown marmorated stink bug (BMSB), Halyomorpha halys Stål (Heteroptera: Pentatomidae). For this purpose, we first identified the spectral and temporal characteristics that best elicit male responsiveness. Bioassays were conducted with artificial signals that mimicked the natural female calling signal. Second, we used the acquired knowledge to synthesize new signals endowed with different degrees of attractiveness in single‐ and two‐choice bioassays using a wooden custom‐made T stand. RESULTS: The results from this study showed that males were attracted to female signals along a high range of amplitudes, especially starting from a threshold of 100 μm s −1, a high pulse repetition time (1 s) and frequency peak corresponding to the first harmonic (76 Hz). This resulted in an "optimal" signal for use to attract males, while the choice test in the T arena showed that this signal elicits searching behavior and attracts BMSB males towards a stimulation point. CONCLUSION: We confirm the use of vibrational signals as a strong tool for behavioral manipulation of male BMSB and suggest its possible use in the development of field traps and further management of this pest. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Vibrotaxis experiments allowed us to define the signal parameters that best attract Halyomorpha halys to vibrotraps. In the near future, this strategy of behavioral manipulation could become a new solution for stinkbug pest management.